Biochemical and Physiological Responses of Harmful Karenia mikimotoi to Algicidal Bacterium Paracoccus homiensis O-4 - Ding, Ning; Wang, Yanbing; Chen, Junfeng; Man, Siyu; Lan, Feng; Wang, Chao; Hu, Lijun; Gao, Peike; Wang, Renjun (Frontiers in Microbiology, 2021)
Harmful algal blooms caused by Karenia mikimotoi frequently occur worldwide and severely threaten the marine environment. In this study, the biochemical and physiological responses of K. mikimotoi to the algicidal bacterium Paracoccus homiensis O-4 were investigated, and the effects on the levels of reactive oxygen species (ROS), malondialdehyde content, multiple antioxidant systems and metabolites, photosynthetic pigments, and photosynthetic index were examined. The cell-free supernatant in strain O-4 significantly inhibited K. mikimotoi cell growth. The bacterium caused the K. mikimotoi cells to activate their antioxidant defenses to mitigate ROS, and this effect was accompanied by the upregulation of intracellular antioxidant enzymes and non-enzyme systems. However, the overproduction of ROS induced lipid peroxidation and oxidative damage within K. mikimotoi cells, ultimately leading to algal death. In addition, the photosynthetic efficiency of the algal cells was significantly inhibited by O-4 and was accompanied by a reduction in photosynthetic pigments. This study indicates that O-4 inhibits K. mikimotoi through excessive oxidative stress and impaired photosynthesis. This research into the biochemical and physiological responses of K. mikimotoi to algicidal bacteria provides insights to the prophylaxis and control of harmful algal blooms via interactions between harmful algae and algicidal bacteria.